CDR 2020
DOI: 10.20517/cdr.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-elicited resistance to anti-glioblastoma photodynamic therapy

Abstract: Glioblastoma multiforme is a highly aggressive primary brain malignancy that resists most conventional chemoand radiotherapeutic interventions. Nitric oxide (NO), a short lived free radical molecule produced by inducible NO synthase (iNOS) in glioblastomas and other tumors, is known to play a key role in tumor persistence, progression, and chemo/radiotherapy resistance. Site-specific and minimally invasive photodynamic therapy (PDT), based on oxidative damage resulting from non-ionizing photoactivation of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The most important candidate that influences the PDT sensitivity is the protein family associated with redox reactions. Oxidative stress-related proteins, such as superoxide dismutase [ 94 ], catalase [ 95 ], and NO synthase [ 96 ], are reported to affect PDT sensitivity. Glutathione and related proteins, such as glutathione peroxidase, glutathione-S-transferase, glutathione transferase omega-1, and glutathione synthase, are also thought to be associated with cell resistance to PDT [ 94 , 97 , 98 ].…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…The most important candidate that influences the PDT sensitivity is the protein family associated with redox reactions. Oxidative stress-related proteins, such as superoxide dismutase [ 94 ], catalase [ 95 ], and NO synthase [ 96 ], are reported to affect PDT sensitivity. Glutathione and related proteins, such as glutathione peroxidase, glutathione-S-transferase, glutathione transferase omega-1, and glutathione synthase, are also thought to be associated with cell resistance to PDT [ 94 , 97 , 98 ].…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…The authors of [ 118 ] found a positive correlation between the high iNOS expression and TNM staging of breast cancer. The increased iNOS activity was also found in tissue samples of colorectal cancer [ 119 ], which plays a crucial role in the angiogenesis of this type of neoplasm [ 120 ], in patients with bladder cancer [ 121 ], who are accompanied with high NO levels in tumor tissues, urine, and blood serum [ 52 , 122 ], with pancreatic cancer [ 123 ], non-small-cell lung carcinoma [ 124 ], as well with head and neck squamous carcinoma [ 125 ], glioblastoma [ 126 ], and melanoma [ 127 ]. In addition, it is associated with a poor prognosis in patients.…”
Section: Role Of Oxidative Stress In Cancer Progressionmentioning
confidence: 99%
“…Rapozzi and colleagues proposed a synergistic effect of NO donors and PS to amplify PDT-mediated cytotoxicity [77,78]. However, accumulating evidence reveals that, in sub-optimal PDT treatments, low-level photodynamic stress can induce NO-mediated tumor resistance and pro-survival effects in different cancer types [79,80]. Since the overall amount of produced NO depends on the PS used, irradiation settings, GSNO concentration, and targeted tissue, the parameters for combined treatment must be carefully determined in clinical settings.…”
Section: Translational Significance Of These Studiesmentioning
confidence: 99%